Functional Characterization of a Lassa Virus Fusion Inhibitor Adaptive Mutant - Jiao Guo; Yalan Du; Guangshun Zhang; Yang Liu; Junyuan Cao; Mengmeng Zhang; Xiaohao Lan; Yueli Zhang; Chenchen Liu; Gengfu Xiao; Wei Wang (Zoonoses, 2025)
Lassa virus (LASV) glycoprotein complex (GPC) contains retained stable-signal peptide (SSP), glycoprotein 1 (GP1), and glycoprotein 2 (GP2). Through serial passaging of LASV with inhibitors, adaptive mutants were obtained, most of which had mutations in the transmembrane (TM) domain of GP2. Characterizing the fusion inhibitor target within the TM domain of GP2 provided insights for the development of drugs and vaccines. We conducted membrane fusion, IIH6 inhibition, thermostability, and viral growth kinetics assays to characterize the effects of the F446L mutation on GPC-mediated membrane fusion, receptor binding, thermostability, growth kinetics, and fitness. F446L conferred cross-resistance to structurally distinct inhibitors. Additionally, F446L increased the fusion activity of LASV and Mopeia virus (MOPV) GPC, thus elevating the pH threshold for LASV fusion and promoting MOPV fusion at neutral pH. However, F446L exerted little effect on the pseudotype viral growth profile or thermostability. Introduction of other residues at the conserved F446 locus indicated that this site showed low compatibility with similar retained aromatic cyclic tyrosine residues and did not tolerate charged residues. We characterized the effects of the F446L mutation on LASV, thus providing useful information for the development of vaccines and drugs.